Impact Of IEC Activity on Women’s Knowledge Through Health Exhibition Arranged on Women’s Day - Patil, Reshma Sudhir (National Journal of Community Medicine, 2011)
Though nutrition interventions have been made in India, significant improvement in nutritional status has not occurred especially in women and girls. Nutritional disorders like anemia, poor weight gain in pregnancy and poor caring practices in girls are still common in all socio-economic groups and the due reason for it is women herself. Therefore, IEC activities regarding nutrition in this high-risk group is essential. The present study was planned to impart nutrition education to women who (n=100) attended health exhibition arranged on women’s day 2008. The effectiveness of the activity was evaluated by taking feedback. Maximum women (98) were satisfied with knowledge gained and it was beneficial for them in increasing their awareness regarding health and nutrition. Awareness of women regarding food adulteration has no significant relation with their age (p>0.05). Also, women have shown a positive response for making changes in their attitude towards nutrition and food adulteration.